Considering Speeding Behavior when Designing a Workable Road Pavement at Downgrade Un-signalized Intersection - Sianto, Paulus; Demon, Stephanus Ola; da Costa, Don Gaspar Noesaku (JUTEKS : Jurnal Teknik Sipil, 2024)
Result of field observation shown that the tendency of riders to exceed speed limit also occurred at downgrade road segments, whereas previous study had reported that even on a flat road only riders with braking ability of 6 m/s2 can be avoided from crash due to the presence of unexpected object suddenly appears at 20 m ahead when traveling at around 60 km/h. This might be triggered by lack of information about pavement, geometrical and traffic condition surrounding. The aim of this study is to identify the accident risk at downgrade road segments due to inappropriate speed choice and/or pavement condition. Accident probability was assessed using the safety factor model, i.e., the ratio of available to minimum stopping sight distances. The minimum stopping sight distance was modified from the AASHTO stopping sight distance model, whilst the available stopping sight distance was determined using the average critical gap acceptance of 35 m obtained from field measurement. From the result of simulation, it was found that only riders with a braking ability of greater than 6.57 m/s2 could avoid crash and/or fatal accident safely. Besides, if the difference in braking ability was around 2 m/s2 then it is required a minimum safety distance of 15.1 m between the following motorcyclists. This strongly indicate that a workable road pavement design should be developed based on appropriate speed limit and/or geometrical condition